Irregular plural formula a new vision in light of modern phonology - ALHroob, Baeth (Dirasat: Human and Social Sciences, 2021)
This research aims to explain the changes that occur when the singular (fa’l) ends with a vowel in the irregular plural formula (af’ul), since morphologists and researchers in modern phonology assume that this singular structure has undergone some changes when combined with the verb (af’ul). The researcher presented the views of the old and some researchers in modern phonology, which dealt with the interpretation of the changes in the transformations of the formula, refutation, and response, and then interpreted a voice interpretation that takes into account the linguistic reality, and tries to come up with a new vision that does not need default interpretation, that add to the system of rules for the formulas of irregular plural in Arabic,The study found that the closest to the language reality is that the form of (af’il) us one of the broken plurals, for each single on the form of (fa’l) with a vowel is at the letter.